The influence of the COVID-19 pandemic on the contemporary and expanded situation of urban mobility - Rakytska, Svitlana; Kambur, Olga (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The COVID-19 pandemic has influenced all dimensions of human living, including, exponentially, the road transport situation in large cities. The factors of influence are subjective or objective, and have an multidirectional impact on the degree of traffic congestion, travel time to the destination and the situation of the environment. The characterization of the cumulative influence of these factors involves the use of statistical, analytical methods and models to parallel the situation “before” and “after,” as well as predict its development in the future. Predicated on the information of traffic congestion, it was exposed how the quarantine severity influenced the traffic intensity, particularly the largest cities in Ukraine: Kyiv, Odesa, Kharkiv, Dnipro. The influence of the time factor on the road situation is analyzed, and an assessment is made of how traffic flows are redistributed in accordance with the new conditions. The directions for improving transport accessibility and urban mobility in the context of the epidemic are proven: digital transformation, spreading the network of bike paths, organization of convenient pedestrian paths, nano-districts and micro-districts where everything needed is nearby.
Keywords: urban mobility; traffic monitoring; transport approachability; COVID-19